REVITALISASI DAYA TARIK WISATA DALAM RANGKA PENINGKATAN KUNJUNGAN WISATAWAN (STUDI KASUS: DAYA TARIK WISATA SANGEH, KABUPATEN BADUNG, BALI) - Yuliana, Putu Ririn; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2016)
This research in tourism attractiveness Sangeh with the purpose of seeing the effort to revitalize the carried out by management in order to increase tourist visit use the theory revitalization. The first step done in this research was described the causes of he did the effort to revitalize. The method employed for this study is qualitative method of analyzing data. Data collection is conducted through observation, deep interview, and document study. The technique of determining informants for this research consist of key informant. The results were obtained, that the revitalization efforts are made visible to the revitalization of the theory has been performing well from the arrangement area is a parking area, garden arrangement, security, shop arrangement, increasing the promotion, make an agreement with the village head, cooperate and make agreements with travel agents, participation from the community of participate mutual cooperation and keep visitors, and the support of the district government Badung of training to employees, scored ticket, and giving development fund. With this effort has been able to regain its image Sangeh as a tourist attraction having a worthy tourist attraction nature, an interesting and still natural, so must visited by tourists have to Bali.
Keywords: Revitalization, Tourist Attraction Sangeh.